INDUSTRIALISASI VAGINA: POTRET KEBIJAKAN PELACURAN - Abas, Abas (JPSI (Journal of Public Sector Innovations), 2017)
The issue of prostitution has long existed before, which is believed to have begun since the period of slavery. Even prostitution as a work is often referred to as one of the oldest types of work in the World. Although some Feminist groups before the 1980s convincingly said that prostitution is a sign and a subordinate example of women that will not exist anymore when women get the equation (Jefrey 2009). As Millett puts it, the old form of 'living fossils' of slave relations still exists today (Millet 1975). Even Jeffrey (2009) says that what is most important today is that the current ideology and new economic practice, "Neo-liberalism," in which the tolerance of 'sexual liberty' has been combined with free market ideology to reconstruct prostitution as 'work' law that could be the basis of the national and international sex industry. Therefore, the development of this sector needs to be understood as the commercialization of the subordination of women, and shows how the return of the global sex industry can begin.